FOMO (Fear of Missing Out) and Social Anxiety Among Gen Z Tiktok Users - Resna Amelia; Farida Nurfalah (Indonesian Journal of Multidisciplinary Science, 2026)
The social media platform Tiktok has had a significant impact on the life of Generation Z, especially in terms of their social interactions and mental health. The intensity of use has increased and has resulted in the phenomenon of Fear of Missing Out (FOMO) which is the fear of being out of the loop of information and social activities. The research problem is the nature of the FOMO phenomenon in TikTok users of Generation Z, the extent of social anxiety that occurs in them and the relationship between FOMO and social anxiety in TikTok users. The aim of this study is to analyse the experience of FOMO among Generation Z TikTok users and to understand the association of FOMO with social anxiety. The study had a qualitative approach and a phenomenological method. The data were obtained through in-depth interviews with Generation Z students who actively use TikTok. Also, the data were collected by reviewing the literature from scientific journals and relevant books about FOMO, social comparison, and social anxiety. The results suggest that using TikTok leads to social comparison, FOMO and the need to be constantly connected online. These factors contribute to developing social anxiety that manifests as low self-confidence and concern about the judgment of others. The research revealed a strong link between Generation Z TikTok users and FOMO and social anxiety.